Prolactin as a Potential Biomarker of Glycemic Control in Women with Type 2 Diabetes Mellitus - Hashim Abed Abass; Salih Mahdi Salih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Prolactin, a hormone primarily known for its important role in lactation and reproductive function have recently been implicated in metabolic-processes including glucose regulation. This study aims to investigation the relationship between serum prolactin levels and markers of glucose metabolism—specifically HbA1c and fasting blood glucose (FBG)—in women with T2DM. A cross sectional study was conducted on 100 adult female patients with T2DM, aged 35–50 years. Participants were classified based on HbA1c into three groups: good (≤7.0%), moderate (7.1–8.5%), and poor (≥8.6%) glycemic control. They were also stratified into low, normal, and high prolactin level groups. Serum prolactin was measured by ELISA, HbA1c by HPLC, and FBG using an automated analyzer. Statistical analysis was performed with significance at p ≤ 0.05. Although prolactin levels tended to increase with worsening HbA1c, the difference among HbA1c groups was not statistically significant. However, when stratified by prolactin levels, women in the high prolactin group had significantly higher HbA1c (7.38 ± 1.07%) and FBG (163.21 ± 25.23 mg/dL) compared to those in the low prolactin group (HbA1c: 6.82 ± 0.91%, FBG: 149.22 ± 22.24 mg/dL; p = 0.041 and p = 0.040, respectively). Elevated serum prolactin levels may be associated with poorer glycemic control in women with T2DM. These results showing the potential-role of prolactin hormone as a supplementary test in measuring glucose metabolism.